The Application of the Qur'anic Sign Language Method - Nurulloh, Khodijah Fitria (Indo Consultan Energi, 2024)
The development of the Al-Qur'an sign language in Indonesia is based on the Arabic sign language. This writing aims to describe the method of translating the Indonesian Al-Qur'an into sign language, which is currently developing and transforming into the Kitabah Method and Recitation Method. This method has enabled Indonesian People with Hearing and Speech Sensory Disabilities (PDSRW) to be able to read and understand (communicate) the meanings and intentions of the Al-Qur'an, hadith and other Islamic teachings so that they have an essential role in strengthening spiritual and religious ties. Data collection uses qualitative research methods in the form of library research or library research using the Tahlili method, which is extracted and sourced from various libraries. This research shows that the Al-Qur'an sign language, Kitabah Method and Recitation Method can make it easier for Indonesian PDSRW people to understand the Al-Qur'an. However, standardization is still needed to facilitate access to PDSRW.